Problem Solving Ability Analysis: Systematic Literature Review - Hadi, Hadi; Juandi, Dadang; Rusdiana, Dian (Universitas Sebelas Maret, 2023)
Problem solving ability is a student's capacity in solving questions or commonly called questions. Problem solving ability is an important component in solving student problems in answering questions given by the teacher. In this study, qualitative studies were analyzed on students' problem solving abilities at the elementary, junior high and high school levels between 1999 and 2022. Systematic Literature Review (SLR) which is a study methodology collects primary data that has been published in journals indexed by Sinta and Scopus . Collected 24 articles of data extraction results adjusted to the selection criteria. Qualitative methods were used in data analysis. Data are grouped according to year of publication, level of education, demography, journal indexer, study materials, and study findings. The research findings show that research on problem solving skills is a major trend in the field of social arithmetic from 1999 to 2022. Many studies on problem solving skills have been conducted at the elementary school level in the Java region. However, at all school levels, the ability to solve math problems is still very high. low . Finding the right solution is the most difficult part for students to master in the problem solving process. One of the factors is that students do not fully understand the material. This is a challenge for researchers and educators who conduct research on students' problem solving abilities, especially in fields where problems are rarely investigated.